2018
DOI: 10.1016/j.worlddev.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Is farmer-to-farmer extension effective? The impact of training on technology adoption and rice farming productivity in Tanzania

Abstract: Agricultural training is a potentially effective method to diffuse relevant new technologies to increase productivity and alleviate rural poverty in Sub-Saharan Africa (SSA). However, since it is prohibitively expensive to provide direct training to all the farmers in SSA, it is critically important to examine the extent to which technologies taught to a small number of farmers disseminate to non-trained farmers. This paper investigates the technology dissemination pathways among smallholder rice producers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(131 citation statements)
references
References 60 publications
9
105
0
5
Order By: Relevance
“…Facilitating the establishment of farmer-to-farmer extension provides a strong foundation for sustainable agricultural extension. Farmer-to-farmer extension provides a cost-effective training method for farmers, since trained farmers disseminate their useful knowledge to the non-trained farmer, and the non-trained farmer is eager to adopt the technology used by the trained farmer to increase yield and profit [98]. A strong positive effect of formal education on a farmer's resilience with respect to CC suggests that farmer-to-farmer extension provided by an educated farmer potentially increases the resilience of the recipient.…”
Section: Institutional Factorsmentioning
confidence: 99%
“…Facilitating the establishment of farmer-to-farmer extension provides a strong foundation for sustainable agricultural extension. Farmer-to-farmer extension provides a cost-effective training method for farmers, since trained farmers disseminate their useful knowledge to the non-trained farmer, and the non-trained farmer is eager to adopt the technology used by the trained farmer to increase yield and profit [98]. A strong positive effect of formal education on a farmer's resilience with respect to CC suggests that farmer-to-farmer extension provided by an educated farmer potentially increases the resilience of the recipient.…”
Section: Institutional Factorsmentioning
confidence: 99%
“…Pan y Zhang (2018) encontraron que la capacitación en el uso de los fertilizantes incrementó 40% el conocimiento sobre su manejo. Nakano et al (2018); Baloch y Thapa (2016) encontraron rendimientos mayores en las huertas de productores que recibieron capacitación, pero además observaron que en el tiempo la diferencia en productividad se amplió en comparación con aquellos que no se capacitaron. Orona et al (2006), en un trabajo sobre nogal en la Comarca Lagunera, sugirieron capacitación específicamente en manejo de plagas y enfermedades y uso de sistemas de riego eficientes.…”
Section: Materiales Y Métodosunclassified
“…Una manera de hacer llegar esos desarrollos a los agricultores es la capacitación. De acuerdo con Nakano et al (2018) la capacitación es un método efectivo para difundir las nuevas tecnologías, incrementar la productividad y disminuir la pobreza rural. Dado que la capacitación tiene un alto costo, el reto para estos autores es elegir el mejor método al más bajo costo para llevar los conocimientos a los agricultores (Nakano et al, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Some recent literature has specifically examined the spread of technology from trained farmers to others in their network. Looking at five-year panel data from Tanzania, Nakano et al (2018) found evidence of the diffusion of improved rice technology from trained primary farmers to other farmers in their villages, while Kondylis, Mueller, and Zhu (2017) show large positive effects from training contact farmers on community adoption rates of technology in Mozambique. In their survey of the FFS literature, however, Waddington et al (2014) found limited evidence of diffusion of information from FFS farmers to other farmers in their village.…”
Section: Show and Tell: Causal Impacts Of Field Days On Farmer Learnimentioning
confidence: 99%